MOTIVATIONAL FACTORS RELATED TO THE PERFORMANCE OF NURSES IN THE INPATIENT INSTALLATION AT RUMAH SAKIT TERPADU (RST) DOMPET DHUAFA BOGOR IN 2023 - Alda Cahya Kumala Sari; Fini Fajrini (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
Nurse performance is a work behavior carried out by nurses in providing nursing care to patients in which there is an implementation of an action plan so that the patient's needs are met optimally. Based on the results of a previous study at RST Dompet Dhuafa Bogor, 65.2% of nurses experienced poor performance. This study aims to find out